Relativistic binary pulsars with black-hole companions - Pfahl, E; Podsiadlowski, P; Rappaport, S (American Astronomical Society, 2005)
Binaries containing a stellar mass black hole and a recycled radio pulsar have so far eluded detection. We present a focused investigation of the formation and evolution of these systems in the Galactic disk, highlighting the factors that limit their numbers and the reasons why they may be extremely rare. We surmise that the birthrate of black hole/recycled pulsar binaries in the Galactic disk is probably no higher than ~10-7 yr-1 and may be much less, including zero. Simple arguments regarding common-envelope evolution suggest that these binaries should have orbital periods <10 hr and an average lifetime of lesssim108 yr before coalescence due to the emission of gravitational radiation. We expect that fewer than ~10 of these compact, relativistic binaries currently reside in the Galactic disk, less than 0.1%-1% of the number of double neutron stars. The discovery of two or more black hole/recycled pulsar binaries using current radio telescopes would tightly constrain certain ideas regarding the evolution of massive stars, dynamical mass transfer, and black hole formation.2